Saudi-Iranian Rapprochement And Its Implications For The Security And Stability Of The Middle East: A Case Study Of Yemen And Syria - Ali, Hemn Shawkat (JURNAL TAPIS, 2023)
This research paper investigates the implications of Saudi-Iranian rapprochement for Middle East security and stability, with a particular focus on Yemen and Syria as case studies. Iran and Saudi Arabia, as the most prominent regional actors in the Middle East, are also viewed as rivals due to their political and geographical positions. The Middle East's security and stability have been threatened by the ongoing rivalry between Saudi Arabia and Iran over the past two decades. As a result, both countries have been involved in multiple proxy wars in Yemen and Syria, as well as the Sunni-Shia sectarian conflict in the region. The study highlights the multifaceted effects of Saudi-Iranian rapprochement on ongoing wars, security dynamics, and Middle Eastern stability by examining the case studies of Yemen and Syria. This study seeks to address the following inquiries: What major factors have prompted the two states to engage in negotiations and even consider resuming diplomatic relations? What are the ramifications of this rapprochement on the security and stability of the region, with a particular focus on Yemen and Syria?  This study improves our knowledge of the complex Saudi-Iranian relationship and its consequences for regional security. The insights gained from the case studies of Yemen and Syria provide significant perspectives on the broader ramifications of the Saudi-Iranian rapprochement. These findings can assist policymakers, scholars, and stakeholders in comprehending the shifting dynamics of the Middle East and fostering increased stability and security in this region.